PENGEMBANGAN MEDIA PEMBELAJARAN MODUL BERBASIS GAMBAR PADA MATERI IPS TERPADU SISWA KELAS VIII SMP NEGERI 3 BATANGHARI NUBAN LAMPUNG TIMUR - Oktavia Oktavia; Elis Setiawati; Tiara Anggia Dewi (Universitas Muhammadiyah Metro, 2021)
This Integrated Social Media learning media refers to an image based learning media module. The image is a combination of points, lines, fields, and colors that are useful for telling something. This method can also be used by students to arouse their interest in learning, language skills, and help them interpret and memorize the contents of material from textbooks. The results of the pre-survey to teachers and students of class VIII of SMP Negeri 3 Batanghari Nuban East Lampung showed that the learning media used were only limited to worksheets while printed books were already available at school but had not been maximally utilized by teachers. Then the researcher makes the development of a valid and practical image-based learning media module that can be used by students. This study uses research procedures and ADDIE development models. This development model consists of 5 stages of development, namely Analysis, Design, Development, Implementation, and Evaluation. The results showed that the image-based module learning media was appropriate to be used in learning. This is shown by the results of expert tests on the appearance of the design of instructional media based on images included in the criteria of